(untitled) (Baghdad Science Journal, 2015)
Diabetes mellitus, or simply diabetes, is a group of metabolic diseases in which a person has high blood sugar, either because the pancreas does not produce enough insulin, or because cells do not respond to the insulin that is produced. This high blood sugar produces the classical symptoms of polyuria (frequent urination), polydipsia (increased thirst), and polyphagia (increased hunger). The aim of the study is to measure several biochemical parameters in T2DM patients and the effect of these parameters in development the disease. Laboratory investigations including Ceruloplasmin , fasting blood glucose (FBG) , malondialdehyde (MDA), serum protein, uric acid, and protein electrophoresis have been measured in patients with type 2 diabetes. Blood samples were obtained from the patients and matching group of healthy volunteer subjects were considered as control group who came to the AL-Yarmok hospital for health checkup.There were significant differences in ceruloplasmin , FBG, malondialdehyde (MDA) , total protein, and uric acid,in the patients when compared to control group. There was a negative correlation between MDA [? mol/l] with ceruloplasmin [mg/dl/] (r=0.43, p